Biofertilizers in the function of sustainable development - Cvijanović, Gorica; Dozet, Gordana; Mićanović, Danica (Economics of Agriculture, 2010)
The concern about the conservation of natural resources is present in almost all countries today. In the past, environmental protection has been reduced to the protection of nature only, through the protection of plants and animals in the protected areas. Through the development of both technology and environmental consciousness process of improving the environment in all areas has become accepted. Simultaneously the methods and guidelines for the process have been defned in the worl as well as in the EU. Commitment of the Republic of Serbia to join the EU means adopting system oriented documents regarding the protection of the environment, organic food production and "soil health" protection. The research is focused on the implementation of biofertilizers as alternative or supplement of mineral fertilizers in crop production, which would ensure the economical production while maintaining a stable yield and environmental protection in the system of sustainable agriculture. The results of this research show that biofertilizers can be successfully used for the protection of the environment and food production, and as such may encourage rural development.